Working on the Artistic Characteristics of Performance in the Teaching of Instruments and Ensemble for Students of Higher Education Music - Ashurov Marufjon Abdumutalibovich (Researchparks Publishing, 2021)
Every teacher has their own style. However, it is important to be able to arouse students' interest in the instrument being taught from the earliest stages of teaching. If a teacher has earned the respect of the students, through the durmat towards that teacher, the student will develop a love for the instrument he is learning. This article reveals ways to work on the artistic features of performance in teaching the subject of instrumental performance and ensemble to students of higher education music.